2015
DOI: 10.3390/f6082631
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Prediction Using Three Alternative Sampling Methods for Seven Sierra Nevada Conifer Species

Abstract: Prediction of projected tree leaf area using allometric relationships with sapwood cross-sectional area is common in tree-and stand-level production studies. Measuring sapwood is difficult and often requires destructive sampling. This study tested multiple leaf area prediction models across seven diverse conifer species in the Sierra Nevada of California. The best-fit whole tree leaf area prediction model for overall simplicity, accuracy, and utility for all seven species was a nonlinear model with basal area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
8
0
4
Order By: Relevance
“…Cross-sectional sapwood area (SA) is commonly used as a scaling parameter to obtain tree sap flow rates and is considered a strong predictor of tree-and plot-level leaf area, leaf biomass, and leaf area index [1][2][3][4][5][6][7][8][9][10]. Studies have reported that sapwood depth has a high correlation with diameter at breast height and sapwood area [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional sapwood area (SA) is commonly used as a scaling parameter to obtain tree sap flow rates and is considered a strong predictor of tree-and plot-level leaf area, leaf biomass, and leaf area index [1][2][3][4][5][6][7][8][9][10]. Studies have reported that sapwood depth has a high correlation with diameter at breast height and sapwood area [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently insufficient data to determine if these findings hold true for other tree species; therefore, more research into intraspecific variation in carbon is necessary in order to determine if carbon fraction varies predictably between wood types within trees. Differences between carbon fractions in heartwood and sapwood could also lead to significant differences in carbon mass estimates across tree sizes, as the heartwood to sapwood proportion is not constant across tree sizes [34].…”
Section: Introductionmentioning
confidence: 99%
“…SLA is an important conversion factor for estimating LA [37,60]. This study found that SLA values increased from top to bottom of a MB crown (Figure 3).…”
Section: Specific Leaf Areamentioning
confidence: 72%
“…Previous studies reported many allometric relationships with accessible tree traits as independent variables to estimate LAs of several specific tree species. These allometries generally relate LA to tree characteristics such as diameter at breast height (DBH) and tree height (H) [13,[35][36][37]. However, there are no validation studies to prove the reliability of the estimated LA of MB by indirect methods.…”
Section: Of 17mentioning
confidence: 99%